PENENTUAN HARGA OPSI EROPA MODEL TRINOMIAL DENGAN TEKNIK EKSTRAPOLASI - , IKHA FITRIA HERDYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research on how option pricing has continued to experienced over time. One of them is by describing stock price movements that follow the trinomial tree model. With this model, it is assumed that the movement of stock prices for the period ahead following three conditions: stock prices will increase, tend to constant, or it will decline. However, the results have a slow convergence so it is required a method to accelerate the convergence with the extrapolation. A frequently used method of extrapolation is the Richardson extrapolation technique which is quite popular extrapolation technique. The initial idea of the use of Richardson extrapolation technique is to do elimination on some early part of the asymptotic expansion from approached function that depends on the stepsize line to get a better approach.